Air stripping pre-treatment process to enhance biogas production in anaerobic digestion of chicken manure wastewater. (June 2021) - Fakkaew, Krailak; Polprasert, Chongrak
Abstract: Anaerobic digestion is typically applied for water and air pollution control and energy recovery from chicken manure wastewater. Unfortunately, high nitrogen content of the chicken manure could be prohibitive to efficient anaerobic digestion. In this study, air stripping was employed as a pre-treatment process for ammonia removal from a chicken manure wastewater. Laboratory-scale experiments of air striping were conducted at various temperatures, initial pH values, air flow rates, and stripping times. The experimental results showed that the high ammonia removal efficiencies of more than 80% could be achieved from the air stripping process operating at the initial pH, temperature, and air flow rate of 11, 80 °C, and 4.0 L/min, respectively. The ammonia removal kinetics were found to fit with the first-order reaction. Bio-methane potential tests suggested that air stripping pre-treatment of the chicken manure wastewater resulted in about 25% increase in biogas production. Graphical abstract: Unlabelled Image Highlights: Air stripping could be applied to remove ammonia from chicken manure wastewater. Temperature, pH, and air flow rate had effects on NH3 removal efficiency. Ammonia removal kinetics were found to fit with the first-order reaction. Applying air stripping in AD resulted in increased biogas production of 25%.